Perilaku Bisnis Petani Pada Usahatani Padi Sawah Non Irigasi di Kabupaten Timor Tengah Utara, Provinsi Nusa Tenggara Timur - Yosefina Marice Fallo (AGRIMOR, 2023)
The cultivation of typical non-irrigated rice fields in the North Central Timor Regency has not been able to provide satisfactory performance for non-irrigated rice field farmers. This research was conducted to examine the factors that influence business behavior and their impact on the performance of non-irrigated lowland rice farming in the North Central Timor District. This study uses 100 samples. Samples were selected randomly using a simple random sampling method. Data were analyzed using the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach. Based on the results of hypothesis testing, it shows that the characteristics of farmers do not affect entrepreneurial behavior. Characteristics of non-irrigated lowland rice farmers that do not affect entrepreneurial behavior are related to low farmer motivation. Many local farmers do business to continue the family business. Only a small portion of farmers aspire to entrepreneurship on this farm. On average, local farmers have high enough confidence in the success of their businesses. With a low level of motivation, and many farmers with a low level of education, all these factors do not affect entrepreneurial behavior. The business environment has a significant effect on entrepreneurial behavior. The coefficient of the business environment variable has a positive sign of 0.670 meaning that an increase in a more conducive business environment means that entrepreneurial behavior is increasing or good. The construct variable with the largest outer loading is the ease of obtaining production facilities. The average farmer's perception of the ease of production facilities is in the sufficient category. This means that not all farmers can access production inputs easily. For seeds, local farmers have been able to provide them independently.